The Nehari manifold approach for a $p(x)$ -Laplacian problem with nonlinear boundary conditions - Fallah, K.; Rasouli, S. H. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We consider a class of $p(x)$-Laplacian equations that involve nonnegative weight functions with nonlinear boundary conditions. Our technical approach is based on the Nehari manifold, which is similar to the fibering method of Drabek andPohozaev, together with the recent idea from Brown and Wu.